Medication Adherence During Pregnancy: A Hospital-Based Cross-Sectional Study in Bandung, Indonesia - Putri RE; Zakiyah N; Puspita F; Alfian SD (Patient Preference and Adherence)
Restika E Putri,1 Neily Zakiyah,1,2 Falerina Puspita,3 Sofa D Alfian1,2 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, Indonesia; 3Department of Pharmacy, Bandung Kiwari General Hospital, Bandung, IndonesiaCorrespondence: Sofa D Alfian, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Jatinangor, KM 21 Jatinangor, Sumedang, Indonesia, Tel/Fax +62-022-7796200, Email sofa.alfian@unpad.ac.idBackground: Nonadherence to medication is common during pregnancy, as pregnant women often have concerns about the safety of the medications they are taking. This study aimed to assess medication adherence levels among pregnant women for various medications and to identify factors associated with nonadherence.Methods: We conducted an observational cross-sectional study among pregnant women who had used at least one medication in the past month at a hospital in Bandung City, West Java, Indonesia. Medication adherence was assessed using the Medication Adherence Report Scale (MARS-5), while medication beliefs were measured with the Beliefs about Medicine Questionnaire (BMQ). Binary logistic regression was used to evaluate the association between medication beliefs, sociodemographic factors, and medication adherence. Odds ratios (ORs) with 95% confidence intervals (CIs) were reported.Results: Among the 235 pregnant women, the adherence levels for each group were as follows: 60.5% for the pregnancy supplements and hormones group, 53.8% for the chronic condition medicines group, 100% for the antibiotics group, and 46.2% for the symptomatic medicines group. A small sample size led to perfect adherence in the antibiotics group. Factors associated with non-adherence were higher harm beliefs (OR 1.20, 95% CI 1.02– 1.40) and negative beliefs (OR 2.42, 95% CI 1.09– 5.33) for the pregnancy supplements and hormones group; negative beliefs (OR 5.16, 95% CI 1.44– 18.4) for the chronic medication group; not being in the first pregnancy (23.92, 95% CI 1.08– 530.55) and the use of more than two types of medicines (OR 29.55, 95% CI 1.06– 825.08) for symptomatic medications.Conclusion: Medication adherence during pregnancy, especially to chronic condition medications, remains low, highlighting the urgent need for intervention. One of the main factors associated with this low adherence during pregnancy is negative beliefs about medications. Tailored counselling on medication use during pregnancy is necessary to address these misconceptions and improve medication adherence in pregnancy.Keywords: medication adherence, pregnant women, medication beliefs, pharmacotherapy